Work Motivation and Caring Behaviour: A Correlation Study in Nursing Practice - Risqi, Nurainni; Sintari, Silvia Ni Nyoman; Subhaktiyasa, Putu Gede (International Journal of Multi Discipline Science (IJ-MDS), 2024)
The primary purpose of this study was to determine and explain the relationship between work motivation and nurses' caring behaviour. The study was quantitative with a cross-sectional approach. The study sample consisted of 70 nurses in the surgical inpatient department at one of the central government hospitals in Bali Province, determined by purposive sampling technique. Data were collected by involving enumerators and analyzed using Kendall's Tau b test. The study results indicated a significant relationship between work motivation and nurses' caring behaviour. The higher the work motivation, the better the nurses' caring behaviour, but the relationship was not more than medium. This finding explains the importance of motivating nurses in providing nursing care. Hospital management can develop strategies that can encourage nurses' intrinsic and extrinsic motivation by considering the variables of this study.